Crohn's Disease Increases In-Hospital Lengths of Stay, Medical Complications, and Costs of Care following Primary Total Knee Arthroplasty - Hadid, Bana; Buehring, Weston; Mannino, Angelo; Weisberg, Miriam D.; Golub, Ivan J; Ng, Mitchell K; Razi, Afshin E. (The Journal of Knee Surgery, 2021)
The literature has shown an increase in prevalence of Crohn's disease (CD) within the United States alongside a concomitant rise in primary total knee arthroplasty (TKA) procedures. As such, with these parallel increases, orthopaedic surgeons will invariably encounter CD patients requiring TKA. Limited studies exist evaluating the impact of this disease on patients undergoing the procedure; therefore, this study endeavors to determine whether CD patients undergoing primary TKA have higher rates of (1) in-hospital lengths of stay (LOS), (2) medical complications, and (3) episode of care (EOC) costs. To accomplish this, a nationwide database was queried from January 1, 2005 to March 31, 2014 to identify patients undergoing TKA. The study group, patients with CD, was randomly matched to the controls, patients without CD, in a 1:5 ratio after accounting for age, sex, and medical comorbidities associated with CD. Patients consuming corticosteroids were excluded, as they are at risk of higher rates of adverse events following TKA. This query ultimately yielded a total of 96,213 patients, with 16,037 in the study cohort and 80,176 in the control one. The study compared in-hospital (LOS), 90-day medical complications, and day of surgery and total global 90-day EOC costs between CD and non-CD patients undergoing primary TKA. The results found CD patients undergoing primary TKA had significantly longer in-hospital LOS (4- vs. 3 days, p < 0.0001) compared with non-CD patients. CD patients were also found to have significantly higher incidence and odds of 90-day medical complications (25.31 vs. 10.75; odds ratio: 2.05, p < 0.0001) compared with their counterparts. Furthermore, CD patients were found to have significantly higher 90-day EOC costs ($15,401.63 vs. 14,241.15, p < 0.0001) compared with controls. This study demonstrated that, after adjusting for age, sex, and medical comorbidities, patients with CD have prolonged in-hospital LOS, increased medical complications, and higher EOC costs following primary TKA. Therefore, it establishes the importance for orthopaedists to adequately counsel CD patients of the potential complications and outcomes following their procedure.
Keywords: total knee arthroplasty; Crohn's disease; in-hospital lengths of stay; 90-day medical complications; costs of care